Sliding composition, use thereof, and method for producing sliding composition
By optimizing components in the olefin-based thermoplastic elastomer composition, including ethylene-α-olefin-non-conjugated polyene copolymer, propylene resin, high-density polyethylene, etc., and crosslinking through phenolic resin-based crosslinking agent, the problems of insufficient bonding, material adhesion, concave and convexity and thermal aging resistance of the sliding composition in the prior art are solved, and multiple properties optimization of the molded body is achieved.
Patent Information
- Application Number
- CN202380065502.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-14
- Filing Date
- 2023-09-13
- Publication Date
- 2025-04-25
AI Technical Summary
When the conventional olefin-based thermoplastic elastomer composition contains silicone-based additives, there are problems such as bonding, adhesion of deposits, concave and convexity of the surface of the molded product, and insufficient heat-resistant aging and sliding characteristics.
A sliding composition is adopted, which comprises ethylene-α-olefin-nonconjugated polyene copolymer, propylene random copolymer, propylene homopolymer, high-density polyethylene, ultra-high molecular weight polyethylene and organic silicon compound, and is cross-linked by a phenolic resin-based crosslinking agent to optimize the component ratio to improve the sliding characteristics, adhesion and heat aging resistance of the molded body.
The sliding composition has excellent balance between sliding characteristics, corner adhesiveness, extrusion moldability, appearance and heat aging resistance in molded bodies such as glass guide grooves, and many problems in the prior art have been solved.
Smart Images

Figure BDA0005307870970000201 
Figure BDA0005307870970000202 
Figure BDA0005307870970000331
Abstract
Description
Technical Field
[0001] One embodiment of the present invention relates to a sliding composition, use of the sliding composition, or a method for producing the sliding composition. Background Art
[0002] Olefin thermoplastic elastomers are lightweight and easy to recycle, and do not generate toxic gases when incinerated. Therefore, from the perspective of energy saving and resource conservation, and in recent years, from the perspective of protecting the global environment, they are widely used as substitutes for vulcanized rubber, especially for automobile parts, industrial machinery parts, electrical / electronic parts, building materials, etc. An example of such an automobile part is a glass run channel.
[0003] A glass run channel is a sealing material (guide member) provided between a window glass and a window frame and is required to have sliding properties with respect to the glass. Therefore, existing products include thermoplastic elastomer compositions containing silicone-based additives and microparticles composed of polyethylene or the like in a thermoplastic elastomer (particularly, compositions having sliding properties are sometimes referred to as "sliding compositions").
[0004] Patent Document 1 describes a structure in which a glass sliding layer bonded to a glass run channel body contains high-density polyethylene, a nonpolar elastomer, and a lubricant (silicon masterbatch) (Example 8).
[0005] Patent Document 2 describes that a glass run channel composed of a composition in which a silylated polyolefin is blended with a thermoplastic elastomer has excellent adhesion and abrasion resistance between a base layer and a skin layer.
[0006] Patent Document 3 describes that a glass run channel made of a composition in which fine particles made of high-density polyethylene and a silicone masterbatch are blended into a thermoplastic elastomer has excellent appearance, friction coefficient, and sliding properties.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 10-193985
[0010] Patent Document 2: Japanese Patent Application Publication No. 2015-189088
[0011] Patent Document 3: Japanese Patent No. 6976862 Summary of the invention
[0012] Problems to be solved by the invention
[0013] However, the present inventors have studied the extrusion moldability of an olefin-based thermoplastic elastomer composition (sliding composition) containing silicone additives and microparticles composed of polyethylene and the like, and found that in the case of a formulation containing silicone additives, adhesion problems sometimes occur at the corners, and foreign matter called deposits attached to the die of the molding machine adheres to impair processability. In addition, it was found that large irregularities were generated on the surface of the molded product, and the appearance of the molded product was impaired. In addition, it can be seen that there is room for improvement in heat aging resistance and sliding properties.
[0014] One embodiment of the present invention provides a sliding composition capable of producing a molded product such as a glass run channel having both sliding properties and adhesion to corners and having an excellent balance among extrusion moldability, appearance, heat aging resistance, etc., and a method for producing the sliding composition.
[0015] Means for solving problems
[0016] The configuration examples of the present invention are as follows. [1]
[0018] A sliding composition comprising:
[0019] 7.0% by mass or more of ethylene-α-olefin-non-conjugated polyene copolymer (A),
[0020] 6.0% by mass or more of a propylene random copolymer (B1) having a melt flow rate of 0.1 to 4.0 g / 10 min as measured at 190° C. and a load of 2.16 kgf,
[0021] 10.0% by mass or more of a propylene homopolymer (B2) having a melt flow rate of 0.1 to 4.0 g / 10 min as measured at 190° C. and a load of 2.16 kgf,
[0022] Density: 940~970kg / m 3 15.0% by mass or more of a high-density polyethylene (C1) having a melt flow rate of 0.1 g / 10 min or less measured at 190° C. and a load of 2.16 kgf,
[0023] The intrinsic viscosity [η] measured in a decalin solvent at 135°C is 10 to 40 dl / g, and the average particle size D 50 22~50μm, density less than 940kg / m 3 10.0 mass % or more of ultra-high molecular weight polyethylene (C2), and
[0024] 5.0 to 8.0% by mass of an organosilicon compound (D) having a kinematic viscosity of 3,000 to 1,000,000 cSt at 25°C (wherein the total content of the above-mentioned components (A), (B1), (B2), (C1), (C2) and (D) is 100.0% by mass or less),
[0025] At least a part of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is crosslinked with a phenolic resin-based crosslinking agent. [2]
[0027] The sliding composition according to [1] further comprises 0.1 to 10.0 mass % of a softener (E) (wherein the total content of the above components (A), (B1), (B2), (C1), (C2), (D) and (E) is 100.0 mass % or less).
[0028] The weight average molecular weight of the above-mentioned ethylene-α-olefin-non-conjugated polyene copolymer (A) is 280,000 or more, the intrinsic viscosity [η] measured in decalin at 135°C is 3.4 dl / g or more, the content of structural units derived from ethylene is 70% by mass or less (wherein the total content of structural units derived from ethylene and structural units derived from α-olefin is 100% by mass), and the content of structural units derived from non-conjugated polyene accounts for 6.0% by mass or less of all structural units of the copolymer (A). [3]
[0030] The sliding composition according to [1] or [2], wherein the Shore D hardness (after 5 seconds) measured in accordance with ISO 7619 is 30 to 60. [4]
[0032] The sliding composition according to any one of [1] to [3], wherein the content of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is 7.0 to 10.0% by mass. [5]
[0034] The sliding composition according to any one of [1] to [4], wherein the total content of the propylene random copolymer (B1) and the propylene homopolymer (B2) is 20.0% by mass or more. [6]
[0036] The sliding composition according to any one of [1] to [5], wherein the content of the propylene random copolymer (B1) is 9.0 to 15.0% by mass, and the density of the propylene random copolymer (B1) is 900 to 920 kg / m 3 . [7]
[0038] The sliding composition according to any one of [1] to [6], wherein the content of the propylene homopolymer (B2) is 10.0 to 18.0% by mass, and the density of the propylene homopolymer (B2) is 900 to 920 kg / m 3 . [8]
[0040] The sliding composition according to any one of [1] to [7], wherein the mass ratio [(B2) / (B1)] of the propylene homopolymer (B2) to the propylene random copolymer (B1) is 1.0 to 3.0. [9]
[0042] The sliding composition according to any one of [1] to [8], wherein the content of the ultrahigh molecular weight polyethylene (C2) is 10.0 to 30.0% by mass, and the average particle size D 50 22~30μm.
[10]
[0044] A molded article obtained by molding the sliding composition according to any one of [1] to [9].
[11]
[0046] A glass run channel comprising the molded body described in
[10] .
[12]
[0048] A method for producing a sliding composition, the sliding composition comprising:
[0049] 7.0% by mass or more of ethylene-α-olefin-non-conjugated polyene copolymer (A),
[0050] 6.0% by mass or more of a propylene random copolymer (B1) having a melt flow rate of 0.1 to 4.0 g / 10 min as measured at 190° C. and a load of 2.16 kgf,
[0051] 10.0% by mass or more of a propylene homopolymer (B2) having a melt flow rate of 0.1 to 4.0 g / 10 min as measured at 190° C. and a load of 2.16 kgf,
[0052] Density: 940~970kg / m 3 15.0% by mass or more of a high-density polyethylene (C1) having a melt flow rate of 0.1 g / 10 min or less measured at 190° C. and a load of 2.16 kgf,
[0053] The intrinsic viscosity [η] measured in a decalin solvent at 135°C is 10 to 40 dl / g, and the average particle size D 50 22~50μm, density less than 940kg / m 310.0 mass % or more of ultra-high molecular weight polyethylene (C2), and
[0054] 5.0 to 8.0% by mass of an organosilicon compound (D) having a kinematic viscosity of 3,000 to 1,000,000 cSt at 25° C. (wherein the total content of the components (A), (B1), (B2), (C1), (C2) and (D) is 100.0% by mass or less), at least a portion of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is crosslinked,
[0055] The method for producing the sliding composition comprises the step of cross-linking at least a portion of the ethylene-α-olefin-non-conjugated polyene copolymer (A) with a phenolic resin-based cross-linking agent.
[0056] Effects of the Invention
[0057] According to the sliding composition of one embodiment of the present invention, it is possible to obtain a molded product such as a glass run channel that can achieve both sliding properties and adhesion at corners and has an excellent balance among extrusion moldability, appearance, and heat aging resistance. DETAILED DESCRIPTION
[0058] Hereinafter, one embodiment of the present invention will be described in detail, but the present invention is not limited to these examples.
[0059] <<Sliding Composition>>
[0060] The sliding composition of one embodiment of the present invention (hereinafter also referred to as "the present composition") comprises: an ethylene-α-olefin-non-conjugated polyene copolymer (A); a propylene random copolymer (B1) having a melt flow rate (MFR) of 0.1 to 4.0 g / 10 min measured at 190°C and a load of 2.16 kgf; a propylene homopolymer (B2) having an MFR of 0.1 to 4.0 g / 10 min measured at 190°C and a load of 2.16 kgf; and a density of 940 to 970 kg / m 3 , a high-density polyethylene (C1) having an MFR of 0.1 g / 10 min or less measured at 190° C. and a load of 2.16 kgf; an intrinsic viscosity [η] of 10 to 40 dl / g measured in a decalin solvent at 135° C., and an average particle size D 50 22~50μm, density less than 940kg / m 3 ultra-high molecular weight polyethylene (C2); and an organosilicon compound (D) having a kinematic viscosity of 3,000 to 1,000,000 cSt at 25°C.
[0061] The present composition is characterized in that at least a part of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is crosslinked with a phenolic resin-based crosslinking agent.
[0062] The content of the component (A) in the present composition is 7.0% by mass or more, preferably 7.0 to 10.0% by mass, more preferably 7.0 to 9.0% by mass, and even more preferably 7.0 to 8.0% by mass, relative to 100.0% by mass of the present composition.
[0063] The content of the component (B1) in the present composition is 6.0% by mass or more, preferably 6.0 to 15.0% by mass, more preferably 6.0 to 13.0% by mass, and even more preferably 6.0 to 11.0% by mass, relative to 100.0% by mass of the present composition.
[0064] The content of the component (B2) in the present composition is 10.0% by mass or more, preferably 10.0 to 18.0% by mass, more preferably 12.0 to 17.5% by mass, and even more preferably 13.0 to 17.0% by mass, relative to 100.0% by mass of the present composition.
[0065] Here, the total content of the above-mentioned component (B1) and the component (B2) is preferably 20.0% by mass or more, more preferably 20.0 to 25.0% by mass, relative to 100.0% by mass of the present composition. In addition, the mass ratio of the component (B1) to the above-mentioned component (B2) [(B2) / (B1)] is preferably 1.0 to 3.0, more preferably 1.2 to 2.8.
[0066] The content of the component (C1) in the present composition is 15.0% by mass or more, preferably 15.0 to 40.0% by mass, more preferably 20.0 to 40.0% by mass, and even more preferably 25.0 to 35.0% by mass, relative to 100.0% by mass of the present composition.
[0067] The content of the component (C2) in the present composition is 10.0% by mass or more, preferably 10.0 to 30.0% by mass, more preferably 10.0 to 25.0% by mass, and even more preferably 10.0 to 20.0% by mass, relative to 100.0% by mass of the present composition.
[0068] Here, the total content of the above-mentioned component (C1) and the component (C2) is preferably 30.0% by mass or more, more preferably 30.0 to 50.0% by mass, relative to 100.0% by mass of the present composition. In addition, the mass ratio of the component (C1) to the above-mentioned component (C2) [(C2) / (C1)] is preferably 0.1 to 1.0, more preferably 0.2 to 0.7.
[0069] The content of the component (D) in the present composition is 5.0 to 8.0% by mass, preferably 5.5 to 8.0% by mass, more preferably 6.0 to 8.0% by mass, and even more preferably 6.0 to 7.5% by mass, relative to 100.0% by mass of the present composition.
[0070] However, the total content of the above-mentioned components (A), (B1), (B2), (C1), (C2) and (D) is 100.0 mass % or less.
[0071] By blending (containing) components (A), (B1), (B2), (C1), (C2) and (D) in the above-mentioned ratio, the present composition can produce a molded product that has both slidability and adhesion to corners and is also excellent in the balance of extrusion moldability, appearance and heat aging resistance.
[0072] If the blending amount of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is less than the aforementioned lower limit, the flexibility is lost and wrinkles are generated. On the other hand, if it exceeds the aforementioned upper limit, the slidability tends to deteriorate.
[0073] When the amount of each propylene resin (B) is less than the aforementioned lower limit, the moldability is deteriorated, while when it exceeds the aforementioned upper limit, the flexibility is lost and wrinkles tend to be generated.
[0074] When the content of the high-density polyethylene (C1) is less than the aforementioned lower limit, the sliding property is deteriorated, while when it exceeds the aforementioned upper limit, the high-density polyethylene (C1) tends to become hard and wrinkles are generated.
[0075] When the blending amount of the ultrahigh molecular weight polyethylene (C2) is less than the aforementioned lower limit, the elongation decreases and the low temperature characteristics deteriorate. On the other hand, when it exceeds the aforementioned upper limit, there is a tendency for softening to deteriorate the sliding properties.
[0076] If the amount of the organosilicon compound (D) is less than the lower limit, the sliding property will be poor. On the other hand, if it exceeds the upper limit, the adhesiveness of the corners of the obtained molded article will be reduced and the low-temperature impact strength will tend to be poor.
[0077] Hereinafter, each component will be described in detail.
[0078] [Ethylene-α-olefin-non-conjugated polyene copolymer (A)]
[0079] The ethylene-α-olefin-non-conjugated polyene copolymer (A) is a copolymer containing structural units derived from ethylene, an α-olefin other than ethylene, and a non-conjugated polyene.
[0080] The present composition may contain only one type of copolymer (A), or may contain two or more types.
[0081] The α-olefin is usually an α-olefin having 3 to 20 carbon atoms, and specific examples thereof include propylene, 1-butene, 1-pentene, 4-methylpentene-1, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-nonadecene, 1-eicosene, 9-methyldecene-1, 11-methyldodecene-1, and 12-ethyltetradecene-1. Among them, propylene, 1-butene, 4-methylpentene-1, 1-hexene, and 1-octene are preferred, and propylene is particularly preferred.
[0082] These α-olefins may be used alone or in combination of two or more.
[0083] Specific examples of the non-conjugated polyene include chain non-conjugated dienes such as 1,4-hexadiene, 3-methyl-1,4-hexadiene, 4-methyl-1,4-hexadiene, 5-methyl-1,4-hexadiene, 4,5-dimethyl-1,4-hexadiene, 7-methyl-1,6-octadiene, 8-methyl-4-ethylidene-1,7-nonadiene, and 4-ethylidene-1,7-undecadiene; methyltetrahydroindene, 5-ethylidene-2-norbornene (ENB), 5-methylene-2-norbornene, 5-isopropylidene; Cyclic non-conjugated dienes such as 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,2-norbornene, 4-ethylidene-8-methyl-1,7-nonadiene, etc. are preferred. Among them, 5-ethylidene-2-norbornene, 5-vinyl-2-norbornene, cyclopentadiene, and 4-ethylidene-8-methyl-1,7-nonadiene are preferred.
[0084] The monomers constituting the copolymer (A) (e.g., ethylene, α-olefins other than ethylene, and non-conjugated polyenes) may be monomers obtained only from raw materials derived from biomass, monomers obtained only from raw materials derived from fossil fuels, or a mixture of monomers obtained from raw materials derived from biomass and monomers obtained from raw materials derived from fossil fuels.
[0085] When the total content of the structural unit derived from ethylene and the content of the structural unit derived from the α-olefin having 3 to 20 carbon atoms is set to 100% by mass, the content of the structural unit derived from ethylene in the copolymer (A) is preferably 70% by mass or less, more preferably 55 to 70% by mass, and further preferably 60 to 69% by mass. In addition, when the total content of the structural unit derived from ethylene and the content of the structural unit derived from the α-olefin having 3 to 20 carbon atoms is set to 100% by mole, the content of the structural unit derived from ethylene is preferably 60 to 80% by mole, and more preferably 70 to 80% by mole.
[0086] When the total content of the structural unit derived from ethylene and the content of the structural unit derived from α-olefins having 3 to 20 carbon atoms is set to 100% by mass, the content of the structural unit derived from α-olefins having 3 to 20 carbon atoms in the copolymer (A) is preferably 30% by mass or more, more preferably 30 to 45% by mass, and further preferably 31 to 40% by mass. In addition, when the total content of the structural unit derived from ethylene and the content of the structural unit derived from α-olefins having 3 to 20 carbon atoms is set to 100% by mole, the content of the structural unit derived from α-olefins having 3 to 20 carbon atoms is preferably 20 to 40% by mole, and more preferably 20 to 30% by mole.
[0087] If the content of the structural unit derived from ethylene and the content of the structural unit derived from an α-olefin having 3 to 20 carbon atoms are within the above ranges, a sliding composition having excellent mechanical properties, rubber elasticity, cold resistance and processability tends to be obtained. If the content of the structural unit derived from ethylene is 70% by mass or less and the content of the structural unit derived from an α-olefin having 3 to 20 carbon atoms is 30% by mass or more, the sliding composition tends to have excellent flexibility, rubber elasticity at low temperatures and processability. If the content of the structural unit derived from ethylene is 55% by mass or more and the content of the structural unit derived from an α-olefin having 3 to 20 carbon atoms is 45% by mass or less, the sliding composition tends to have excellent mechanical properties and rubber elasticity at high temperatures.
[0088] In addition, the content of the structural unit derived from the non-conjugated polyene is preferably 6.0% by mass or less of the total structural units of the copolymer (A), more preferably 2.0 to 6.0% by mass, and further preferably 3.0 to 6.0% by mass. If the content of the structural unit derived from the non-conjugated polyene is within the above range, there is a tendency for the molding appearance and heat aging resistance to be excellent.
[0089] The content of each structural unit of the copolymer (A) can be determined by 13 C-NMR method can be used for measurement, and peak identification and quantification can be performed according to the method described below or the method described in "Handbook of Polymer Analysis" (published by Asakura Bookstore in 2008, first edition, pages 184 to 211).
[0090] The intrinsic viscosity [η] of the copolymer (A) measured in decalin at 135° C. is preferably 3.4 dl / g or more, more preferably 3.4 to 6.0 dl / g, and still more preferably 3.4 to 5.5 dl / g. When the intrinsic viscosity [η] measured in decalin at 135° C. is within the above range, a slidable composition having an excellent balance among mechanical properties, rubber elasticity, and processability tends to be obtained.
[0091] The intrinsic viscosity [η] can be measured by the method described in Examples below.
[0092] The iodine value of the copolymer (A) measured in accordance with JIS K 0070: 1992 is preferably 2 to 50 g / 100 g, more preferably 5 to 40 g / 100 g, and still more preferably 7 to 30 g / 100 g. If the iodine value is lower than the lower limit, the crosslinking efficiency in the thermoplastic elastomer described below may be reduced, and the rubber elasticity may be reduced. If the iodine value is higher than the upper limit, the crosslinking density may be too high, the elongation may be reduced, and the physical property balance may be deteriorated.
[0093] The weight average molecular weight (Mw) of the copolymer (A) measured by GPC is preferably 280,000 or more, more preferably 280,000 to 500,000. In addition, the molecular weight distribution (Mw / Mn) is usually 1.5 to 50, preferably 1.8 to 30, and more preferably 2.0 to 6. If the molecular weight distribution is lower than the above range, the content of low molecular weight components decreases, and sometimes the processability decreases. If the molecular weight distribution is higher than the above range, the content of low molecular weight components increases, and sometimes the fogging resistance deteriorates.
[0094] The Mooney viscosity (ML) at 100°C of the copolymer (A) measured in accordance with JIS K 6395:2010 1+4 ) is preferably 15 to 400, more preferably 30 to 250. When the Mooney viscosity is within the above range, the balance between mechanical properties and processability tends to be excellent.
[0095] The copolymer (A) can be commercially available or manufactured by a conventionally known method. As a conventionally known method, it can be manufactured by a method described in "Polymer Manufacturing Process ((strain) Industrial Research Association, issued p.309-330)" or Japanese Patent Publication No. 9-71617, Japanese Patent Publication No. 9-71618, Japanese Patent Publication No. 9-208615, Japanese Patent Publication No. 10-67823, Japanese Patent Publication No. 10-67824, Japanese Patent Publication No. 10-110054, International Publication No. 2009 / 081792, International Publication No. 2009 / 081794, etc., which are applied by the applicant of the present application.
[0096] Examples of the olefin polymerization catalyst preferably used in the production of the copolymer (A) include:
[0097] A known Ziegler catalyst comprising a transition metal compound such as vanadium (V), zirconium (Zr), titanium (Ti), or the like and an organoaluminum compound (organoaluminum oxy compound);
[0098] A known metallocene catalyst comprising a metallocene compound of a transition metal selected from Group IV of the periodic table and an organoaluminum oxy-compound or an ionizing ionic compound (for example, a metallocene catalyst described in Japanese Unexamined Patent Publication No. 9-40586);
[0099] A known metallocene catalyst comprising a specific transition metal compound and a co-catalyst such as a boron compound (for example, a metallocene catalyst described in International Publication No. 2009 / 072553);
[0100] A transition metal compound catalyst comprising a specific transition metal compound and an organometallic compound, an organoaluminum oxy-compound, or a compound that reacts with the transition metal compound to form an ion pair (for example, a transition metal compound catalyst described in JP-A-2011-52231).
[0101] In particular, when a metallocene catalyst is used, the distribution of the non-conjugated polyene becomes uniform, and a high crosslinking efficiency can be obtained even if the amount of the non-conjugated polyene introduced is small. In addition, the catalytic activity is high and the chlorine content derived from the catalyst can be reduced, which is particularly preferred.
[0102] It should be noted that the copolymer (A) may be used as a component (α) containing the copolymer (A), such as a copolymer (hereinafter also referred to as "oil-extended rubber") obtained by mixing a petroleum plasticizer (softener) and the copolymer (A) in advance and oil-extending before mixing with the components other than the copolymer (A) described later. Examples of the petroleum plasticizer include the same "petroleum plasticizer" as exemplified in the softener (E) of [other components] described later.
[0103] As a method for producing the oil-extended rubber (oil-extending method), a conventionally known method may be used. For example, the following methods may be mentioned: a method of mechanically kneading the copolymer (A) and a petroleum plasticizer using a mixing roll or a Banbury mixer to perform oil-extending; a method of adding a predetermined amount of a petroleum plasticizer to the copolymer (A) and then removing the solvent by steam stripping or the like; a method of impregnating a mixture of a crumb-like copolymer (A) and a petroleum plasticizer by stirring using a Henschel mixer or the like.
[0104] The oil-extended rubber may be a commercially available product, for example, Mitsui EPT manufactured by Mitsui Chemicals, Inc., JSR EPR manufactured by JSR Corporation, ESPRENE (registered trademark) manufactured by Sumitomo Chemical Co., Ltd., Keltan (registered trademark) manufactured by LANXESS Co., Ltd., KEP (registered trademark) manufactured by KUMHOPOLYCHEM Co., Ltd., and NODEL (registered trademark) manufactured by Dow Chemical Co., Ltd.
[0105] [Acrylic resin (B)]
[0106] The present composition comprises a propylene random copolymer (B1) and a propylene homopolymer (B2) as the propylene resin (B). The propylene random copolymer (B1) is a copolymer of propylene and α-olefin (propylene-α-olefin copolymer), and is a random copolymer.
[0107] The present composition may contain only one type of copolymer (B1) and one type of polymer (B2), respectively, or may contain two or more types.
[0108] <Propylene-based random copolymer (B1)>
[0109] Examples of the α-olefin in the propylene-α-olefin copolymer (B1) include ethylene and α-olefins having 4 to 12 carbon atoms.
[0110] Examples of the α-olefins having 4 to 12 carbon atoms include linear or branched α-olefins such as 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-octene, 1-decene and 1-dodecene.
[0111] The α-olefin may be used alone or in combination of two or more.
[0112] The content of the structural unit derived from propylene in the copolymer (B1) is preferably 60 to 99.5 mol%, more preferably 80 to 99 mol%, further preferably 90 to 98.5 mol%, particularly preferably 95 to 98 mol%.
[0113] The content of the structural unit derived from α-olefin in the propylene-α-olefin copolymer is preferably 0.5 to 40 mol%, more preferably 1 to 20 mol%, further preferably 1.5 to 10 mol%, particularly preferably 2 to 5 mol%.
[0114] Here, the total of the content of the structural unit derived from propylene and the content of the structural unit derived from α-olefin is 100 mol%.
[0115] The propylene-α-olefin copolymer may contain a small amount (e.g., 10 mol% or less based on all the structural units of the propylene copolymer (A)) of structural units derived from olefins other than ethylene and olefins having 3 to 12 carbon atoms.
[0116] The other olefins may be used alone or in combination of two or more.
[0117] The melt flow rate (MFR) of the copolymer (B1) measured at 190°C and a load of 2.16 kgf in accordance with JIS K 7210 is 0.1 to 4.0 g / 10 min, preferably 0.3 to 2.5 g / 10 min, more preferably 0.5 to 2.0 g / 10 min.
[0118] When the MFR of the copolymer (B1) is within the above range, the present composition can be easily injection-molded, and a molded product having an excellent balance between dimensional stability and impact strength can be easily obtained.
[0119] The density of the copolymer (B1) according to JIS K 7112B method (pycnometer method) is preferably 900 to 920 kg / cm 3 , more preferably 910 to 920 kg / cm 3 .
[0120] When the density of the copolymer (B1) is within the above range, the present composition can be easily injection-molded, and a molded product having an excellent balance between dimensional stability and impact strength can be easily obtained.
[0121] <Propylene homopolymer (B2)>
[0122] The melt flow rate (MFR) of the polymer (B2) measured at 190°C and a load of 2.16 kgf in accordance with JIS K7210 is 0.1 to 4.0 g / 10 min, preferably 0.3 to 2.5 g / 10 min, more preferably 0.5 to 2.0 g / 10 min.
[0123] When the MFR of the polymer (B2) is within the above range, the present composition can be easily injection-molded, and a molded product having an excellent balance between dimensional stability and impact strength can be easily obtained.
[0124] The density of the polymer (B2) measured in accordance with JIS K7112 B method (pycnometer method) is preferably 900 to 920 kg / cm 3 , more preferably 910 to 920 kg / cm 3 .
[0125] When the density of the polymer (B2) is within the above range, the present composition can be easily injection-molded, and a molded product having an excellent balance between dimensional stability and impact strength can be easily obtained.
[0126] The copolymer (B1) and the polymer (B2) may be commercially available products or may be appropriately produced by a known method.
[0127] The monomers constituting the copolymer (B1) and / or the polymer (B2) (e.g., propylene and α-olefins other than propylene) may be only monomers obtained from a raw material derived from biomass, only monomers obtained from a raw material derived from fossil fuels, or a mixture of monomers obtained from a raw material derived from biomass and monomers obtained from a raw material derived from fossil fuels.
[0128] The present composition may contain a propylene polymer (B3) other than the copolymer (B1) and the polymer (B2) within a range not impairing the effects of the present invention. Examples thereof include propylene block copolymers (eg, block copolymers of propylene and 30 mol % or less of other α-olefins).
[0129] Examples of commercially available products of the propylene-based resin (B) include Prime Polypro (registered trademark) manufactured by Prime Polymer Co., Ltd., NOVATEC manufactured by Nippon Polypro Co., Ltd., and Sumitomo (registered trademark) NOBLEN (registered trademark) manufactured by Sumitomo Chemical Co., Ltd.
[0130] [Vinyl resin (C)]
[0131] The present composition comprises high-density polyethylene (C1) and ultra-high molecular weight polyethylene (C2) as ethylene resin (C). High-density polyethylene (C1) is a component for achieving both adhesiveness and sliding properties, and ultra-high molecular weight polyethylene (C2) is a component for achieving both extrusion moldability and sliding properties.
[0132] The present composition may contain only one type of high-density polyethylene (C1) and one type of ultra-high molecular weight polyethylene (C2), respectively, or may contain two or more types.
[0133] <High-density polyethylene (C1)>
[0134] Examples of the high-density polyethylene (C1) include ethylene homopolymers and ethylene-α-olefin copolymers.
[0135] Specific examples of the α-olefin in the ethylene-α-olefin copolymer include α-olefins having 3 to 12 carbon atoms, such as propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene.
[0136] The α-olefin may be used alone or in combination of two or more.
[0137] When the high-density polyethylene (C1) is an ethylene-α-olefin copolymer, the content of structural units derived from ethylene is preferably 50 to 99 mol%, more preferably 55 to 99 mol%, and further preferably 55 to 98 mol%. The content of structural units derived from α-olefin is preferably 1 to 50 mol%, more preferably 1 to 45 mol%, and further preferably 2 to 45 mol%.
[0138] Here, the total of the content of the structural unit derived from ethylene and the content of the structural unit derived from α-olefin is 100 mol%.
[0139] The density of the high-density polyethylene (C1) measured in accordance with JIS K7112 B method (pycnometer method) is 940 to 970 kg / cm 3 , preferably 945~965kg / cm 3 .
[0140] When the density of the high-density polyethylene (C1) is within the above range, a molded product having excellent adhesiveness can be easily obtained.
[0141] From the viewpoint of adhesiveness, the melting point of the high-density polyethylene (C1) measured by differential scanning calorimetry (DSC) is preferably 110 to 150° C., more preferably 115 to 150° C., and even more preferably 120 to 140° C. Here, the melting point is the crystal melting peak temperature (Tm) obtained from a thermogram measured by heating about 10 mg of a sample from -40° C. to 200° C. at a heating rate of 10° C. / min using a differential scanning calorimeter, maintaining at 200° C. for 1 minute, cooling to -40° C. at a cooling rate of 10° C. / min, and again heating to 200° C. at a heating rate of 10° C. / min.
[0142] From the viewpoint of improving the sliding property, the MFR of the high-density polyethylene (C1) measured at 190°C and a load of 2.16 kgf in accordance with JIS K 7210 is 0.1 g / 10 min or less, preferably 0.01 to 0.1 g / 10 min, and more preferably 0.01 to 0.50 g / 10 min.
[0143] As the polymerization catalyst used in the production of high-density polyethylene (C1), for example, there can be mentioned well-known multi-site catalysts such as Ziegler series and Phillips series; Kaminsky catalysts such as zirconocene, titanocene, and hafnocenene (collectively referred to as metallocenes), and high-activity single-site catalysts such as post-metallocene catalysts. High-density polyethylene (C1) can be produced by a well-known polymerization method using the polymerization catalyst.
[0144] <Ultra-high molecular weight polyethylene (C2)>
[0145] Examples of the ultra-high molecular weight polyethylene (C2) include ethylene homopolymers and ethylene-α-olefin copolymers.
[0146] Specific examples of the α-olefin in the ethylene-α-olefin copolymer include α-olefins having 3 to 12 carbon atoms, such as propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene.
[0147] The α-olefin may be used alone or in combination of two or more.
[0148] When the ultra-high molecular weight polyethylene (C2) is an ethylene-α-olefin copolymer, the content of structural units derived from ethylene is preferably 50 to 99 mol%, more preferably 55 to 99 mol%, and further preferably 55 to 98 mol%. The content of structural units derived from α-olefin is preferably 1 to 50 mol%, more preferably 1 to 45 mol%, and further preferably 2 to 45 mol%.
[0149] Here, the total of the content of the structural unit derived from ethylene and the content of the structural unit derived from α-olefin is 100 mol%.
[0150] From the viewpoint of improving the sliding property, etc., the ultrahigh molecular weight polyethylene (C2) has an intrinsic viscosity [η] measured in decalin at 135°C of 10 to 40 dl / g, preferably 15 to 35 dl / g, more preferably 20 to 35 dl / g.
[0151] The intrinsic viscosity [η] can be measured by the method described in Examples below.
[0152] Average particle size D of ultra-high molecular weight polyethylene (C2) 50 The thickness is 22 μm to 50 μm, more preferably 22 μm to 40 μm, and even more preferably 22 μm to 30 μm.
[0153] The average particle size can be measured by the method described in Examples below. When the average particle size of the ultrahigh molecular weight polyethylene (C2) is within the above range, a molded product having excellent extrusion moldability can be easily obtained.
[0154] The average particle size [η] can be measured by the method described in Examples below.
[0155] The density of ultra-high molecular weight polyethylene (C2) measured by JIS K7112 B method (pycnometer method) is less than 940 kg / cm 3 , preferably 850~930kg / cm 3 , more preferably 850 to 920 kg / cm 3 .
[0156] When the density of the ultra-high molecular weight polyethylene (C2) is within the above range, a molded product having excellent extrusion moldability can be easily obtained.
[0157] As the manufacturing method of ultra-high molecular weight polyethylene (C2), a known polymerization method using a catalyst for olefin polymerization can be used. For example, preferably, a solution polymerization method, a slurry polymerization method, a high pressure ion polymerization method, a gas phase polymerization method using a complex catalyst such as a Ziegler-Natta catalyst, a metallocene complex, a non-metallocene complex, and a bulk polymerization method, a solution polymerization method, etc. using a free radical initiator are also used to manufacture. Among them, it is particularly preferred to use a method for polymerizing monomers using a Ziegler-Natta catalyst, a complex catalyst, or a method for polymerizing monomers in the presence of a metallocene catalyst.
[0158] The monomers constituting the high-density polyethylene (C1) and / or the ultra-high molecular weight polyethylene (C2) (e.g., ethylene and α-olefins other than ethylene) may be solely monomers obtained from raw materials derived from biomass, solely monomers obtained from raw materials derived from fossil fuels, or a mixture of monomers obtained from raw materials derived from biomass and monomers obtained from raw materials derived from fossil fuels.
[0159] The present composition may contain an ethylene-based polymer (C3) other than the high-density polyethylene (C1) and the ultra-high molecular weight polyethylene (C2) within a range not impairing the effects of the present invention.
[0160] Examples of commercially available products of the ethylene-based resin (C) include Hi-zex (registered trademark) manufactured by Prime Polymer Co., Ltd., MIPELON (registered trademark) manufactured by Mitsui Chemicals, Inc., MIRASON (registered trademark) manufactured by Prime Polymer Co., Ltd., EVOLUE (registered trademark) manufactured by Prime Polymer Co., Ltd., and SUNTEC manufactured by Asahi Kasei Corporation.
[0161] [Organosilicon compound (D)]
[0162] The present composition contains an organosilicon compound (D). The organosilicon compound (D) is a component added mainly to reduce sliding resistance.
[0163] The present composition may contain only one type of the organosilicon compound (D), or may contain two or more types.
[0164] From the viewpoint of reducing sliding resistance, the kinematic viscosity of the organosilicon compound (D) at 25°C is 3,000 to 1,000,000 cSt, preferably 3,000 to 500,000 cSt, and more preferably 3,000 to 200,000 cSt. When a plurality of organosilicon compounds (D) are used, the kinematic viscosity at 25°C of each of them may be within the above range.
[0165] The kinematic viscosity is measured by the method described in Examples below.
[0166] Examples of the organosilicon compound (D) include silicone oil, high molecular weight silicone (silicone rubber), and silicone powder. Preferably, (D-1) silicone oil (preferably with a kinematic viscosity of less than 5000 mm 2 / s silicone oil) is used in combination with (D-2) silicone rubber.
[0167] When the silicone oil (D-1) and the silicone rubber (D-2) are used in combination, the mass ratio [(D-1) / (D-2)] is preferably 90 / 10 to 10 / 90, more preferably 75 / 25 to 25 / 75.
[0168] Examples of the silicone oil include dimethyl silicone oil, phenylmethyl silicone oil, alkyl silicone oil, fluorosilicone oil, tetramethyltetraphenyltrisiloxane, and modified silicone oil.
[0169] The silicone rubber is preferably a silicone rubber having a weight average molecular weight of 100,000 or more, more preferably 100,000 to 800,000, and further preferably 450,000 to 650,000. In addition, the silicone rubber is preferably a non-crosslinked silicone rubber. The weight average molecular weight can be measured, for example, by GPC (gel permeation chromatography).
[0170] The silicone rubber may be a commercial product or a commercial product of a silicone masterbatch pre-mixed with a resin component such as polypropylene. Examples of commercial products include MB50-001 and BY27-001 manufactured by Dow Corning Toray, CF-9150 manufactured by Dow Corning Toray Silicones, and X-21-3043 and X-22-2101 manufactured by Shin-Etsu Chemical Co., Ltd.
[0171] The GPC measurement of the silicone rubber in the masterbatch can be performed by subjecting the masterbatch to, for example, the following treatment in advance to separate the silicone rubber and polypropylene, and then measuring the obtained silicone rubber.
[0172] (Separation of silicone rubber and polypropylene)
[0173] First, weigh 0.05g of the sample (masterbatch), add 10mL of xylene added with 0.1g / L BHT (butylated hydroxytoluene), and stir at 125°C for 60 minutes to dissolve the masterbatch. After visually confirming that the masterbatch is completely dissolved, let the solution stand at room temperature for about 3 hours to allow crystalline polypropylene to precipitate in the liquid. Use Fluoropore FP-100 (1μm) made by Sumitomo Electric Industries to filter the solution with the crystals precipitated, wash with 3mL of xylene, and separate it into CXS (xylene soluble part, silicone rubber) and CXIS (xylene insoluble part, polypropylene). After pre-drying and curing the CXS by blowing nitrogen at room temperature, vacuum drying at 60°C. Vacuum drying is carried out until no weight loss is observed. The CXS part after vacuum drying is used for GPC measurement.
[0174] [Other ingredients]
[0175] The present composition may contain other components other than the above-mentioned (A) to (D) as necessary within a range not impairing the effects of the present invention.
[0176] Examples of the other components include other resins other than the above-mentioned (A) to (C), elastomers, softeners (E), heat stabilizers, antistatic agents, weather stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, fillers, flame retardants, colorants, and lubricants.
[0177] These other components may be used alone or in combination of two or more.
[0178] <Softener (E)>
[0179] As the softener (E), a softener (plasticizer) generally used for rubber can be used. The softener (E) may be a softener obtained from a raw material derived from fossil fuels or a softener obtained from a raw material of an animal or plant.
[0180] Specific examples of the softener (E) include petroleum plasticizers such as process oil, lubricating oil, paraffin oil, liquid paraffin, petroleum asphalt, and vaseline; coal tar plasticizers such as coal tar and coal tar pitch; fatty oil plasticizers such as castor oil, linseed oil, rapeseed oil, soybean oil, and coconut oil; tall oil; factice; waxes such as beeswax, carnauba wax, and lanolin; fatty acids and fatty acid salts such as ricinoleic acid, palmitic acid, stearic acid, barium stearate, calcium stearate, and zinc laurate; cyclohexane acid; pine oil, rosin, or their derivatives; synthetic polymers such as terpene resins, petroleum resins, and coumarone-indene resins; ester plasticizers such as dioctyl phthalate, dioctyl adipate, and dioctyl sebacate; microcrystalline wax, liquid polybutadiene, modified liquid polybutadiene, liquid polysulfide rubber, and hydrocarbon-based synthetic lubricating oils. Among them, petroleum-based plasticizers are preferably used, and process oils such as paraffin-based process oils and naphthenic process oils are particularly preferably used.
[0181] When a softener (E) is added to the present composition, the amount (content) thereof is preferably 0.1 to 10.0% by mass, more preferably 1.0 to 9.8% by mass, relative to 100.0% by mass of the present composition, from the viewpoint of preventing bleeding and improving coating adhesion. The total content of the above-mentioned components (A), (B1), (B2), (C1), (C2), (D) and (E) is 100.0% by mass or less.
[0182] When the oil-extended rubber is used as a raw material of the present composition, the petroleum-based plasticizer used for oil extension is contained in the softener (E).
[0183] <<Method for producing the present composition>>
[0184] The present composition can be produced by melt-kneading an ethylene-α-olefin-non-conjugated polyene copolymer (A), a propylene random copolymer (B1), a propylene homopolymer (B2), a high-density polyethylene (C1), an ultra-high molecular weight polyethylene (C2), an organosilicon compound (D), and other components as required, followed by granulation or pulverization.
[0185] The present composition is characterized in that at least a portion of the copolymer (A) is crosslinked by a phenolic resin crosslinking agent. That is, the method for producing the present composition comprises a step of crosslinking at least a portion of the copolymer (A) by a phenolic resin crosslinking agent. The aforementioned step is not particularly limited as long as it is a conventionally known crosslinking method using a phenolic resin crosslinking agent, and is preferably as follows from the aspects of slip, low temperature characteristics and flexibility.
[0186] A method of dynamically heat treating a mixture containing a copolymer (A), a phenolic resin crosslinking agent, preferably a portion of a propylene resin (B), and other components as required to produce a thermoplastic elastomer in which at least a portion of the copolymer (A) is partially or completely crosslinked by the phenolic resin crosslinking agent (hereinafter also referred to as "thermoplastic elastomer"). The remaining propylene resin (B), high-density polyethylene (C1), ultra-high molecular weight polyethylene (C2), an organosilicon compound (D), and other components as required are melt-kneaded and then granulated or pulverized.
[0187] The kneading can be performed using a kneading device. Examples of the kneading device include a mixing roll, an intensive mixer (eg, a Banbury mixer, a kneader), a single-screw or twin-screw extruder, and a non-open type device is preferred.
[0188] It should be noted that the granulation or pulverization may be performed by a conventionally known method.
[0189] [Thermoplastic elastomer]
[0190] As a raw material of the present composition, a thermoplastic elastomer prepared in advance as described above, in which at least a part of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is partially or completely crosslinked with a phenolic resin crosslinking agent can be used. The thermoplastic elastomer may also contain a propylene resin (B).
[0191] Examples of such thermoplastic elastomers include the following (1) or (2).
[0192] Examples include:
[0193] (1) A partially or completely crosslinked thermoplastic elastomer obtained by dynamically heat treating a mixture comprising (a) a crosslinked olefin copolymer rubber (uncrosslinked rubber) (e.g., copolymer (A)) [hereinafter also referred to as “component (a)”], (b) a crystalline polypropylene (e.g., propylene resin (B)) [hereinafter also referred to as “component (b)”], and, if necessary, (c) a petroleum plasticizer [hereinafter also referred to as “component (c)”] in the presence of a phenolic resin crosslinking agent;
[0194] (2) A partially or completely crosslinked thermoplastic elastomer obtained by uniformly blending (d) the remaining component (b) into a crosslinked rubber composition obtained by dynamically heat treating a mixture containing the component (a), a part of the component (b) and, if necessary, the component (c) in the presence of a phenolic resin crosslinking agent.
[0195] The petroleum plasticizer (c) is generally a high-boiling petroleum fraction used for the purpose of weakening the intermolecular force of the rubber, facilitating the processing, and facilitating the dispersion of carbon black, white carbon, etc., which are optionally contained, or for the purpose of reducing the hardness of the vulcanized rubber and increasing the flexibility and elasticity. Examples of the component (c) include the same plasticizers as those in the [other components] above.
[0196] In the thermoplastic elastomer, the mass ratio of the component (b) to the component (a) [(b) / (a)] is usually 90 / 10 to 10 / 90, preferably 70 / 30 to 15 / 85.
[0197] In addition, as component (a), copolymer (A) and other uncrosslinked rubber may be used in combination. In this case, the other uncrosslinked rubber is preferably used in an amount of 40 parts by mass or less, more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the total amount of component (b) and component (a).
[0198] Examples of the other uncrosslinked rubber include diene rubbers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), natural rubber (NR), and butyl rubber (IIR), SEBS, and polyisobutylene.
[0199] As the aforementioned thermoplastic elastomer, a thermoplastic elastomer is preferably one comprising a propylene resin (B) as a crystalline polypropylene and an ethylene-α-olefin-non-conjugated polyene copolymer (A) as an uncrosslinked rubber, wherein these exist in a partially crosslinked state in the thermoplastic elastomer, and the mass ratio of the crystalline polypropylene to the uncrosslinked rubber [crystalline polypropylene / uncrosslinked rubber] is within a range of 70 / 30 to 10 / 90.
[0200] As a more specific example of the thermoplastic elastomer, there can be mentioned a thermoplastic elastomer in which the uncrosslinked rubber (a-1) is partially crosslinked, obtained by subjecting a mixture comprising 30 to 90 parts by mass of at least one uncrosslinked rubber (a-1) selected from ethylene-propylene-non-conjugated polyene copolymers, 70 to 10 parts by mass of at least one crystalline polypropylene (b-1) selected from propylene random copolymers (B1) (wherein the total amount of components (a-1) and (b-1) is 100 parts by mass), and 5 to 150 parts by mass of a petroleum plasticizer (c) to dynamic heat treatment in the presence of a phenolic resin crosslinking agent.
[0201] The phenolic resin crosslinking agent is a thermoplastic resin, and is also called a phenolic resin curing resin or a phenolic resin. Examples of the phenolic resin crosslinking agent include halogenated phenolic resin crosslinking agents.
[0202] By using the above-mentioned phenolic resin crosslinking agent, a sliding composition having excellent heat aging resistance can be obtained.
[0203] Preferred examples of phenolic resin crosslinking agents include resol phenolic resins, crosslinking agents produced by condensing alkyl-substituted phenols or unsubstituted phenols with aldehydes, preferably formaldehyde, in an alkaline medium, or crosslinking agents produced by condensing bifunctional phenol diols.
[0204] The alkyl-substituted phenol is preferably an alkyl-substituted phenol having about 1 to 10 carbon atoms, and more preferably a dimethylolphenol or a phenolic resin substituted at the para-position with an alkyl group having about 1 to 10 carbon atoms.
[0205] Examples of the phenolic resin crosslinking agent include compounds represented by the following formula (I) or compounds in which the terminal hydroxyl group (—CH 2 —OH) of the compound represented by the following formula (I) is substituted with a halogen atom.
[0206] [Chemistry 1]
[0207]
[0208] (In the formula, Q is -CH2- or -CH2-O-CH2-, m is an integer from 0 to 20, and R' is an organic group.)
[0209] Preferably, Q is -CH2-O-CH2-, m is an integer of 0 to 10, and R' is an organic group having less than 20 carbon atoms. More preferably, m is an integer of 0 to 5, and R' is an organic group having 4 to 12 carbon atoms.
[0210] As a compound obtained by substituting a halogen atom for a terminal hydroxyl group (-CH2-OH) of a compound represented by the aforementioned formula (I) or a compound represented by the aforementioned formula (I), specifically, an alkylphenol formaldehyde resin, a hydroxymethylated alkylphenol resin, a halogenated alkylphenol resin, etc. can be cited, preferably a halogenated alkylphenol resin, and more preferably a bromide obtained by substituting a bromine atom for a terminal hydroxyl group (-CH2-OH) of a compound represented by the aforementioned formula (I). An example of the bromide is shown in the following formula (II).
[0211] [Chemistry 2]
[0212]
[0213] (In the formula, n is an integer of 0 to 10, and R is a saturated hydrocarbon group having 1 to 15 carbon atoms.)
[0214] Examples of the phenolic resin crosslinking agent include Tackirol 201 (alkylphenol formaldehyde resin, manufactured by Taoka Chemical Industry Co., Ltd.), Tackirol 250-I (brominated alkylphenol formaldehyde resin with a bromine content of 4%, manufactured by Taoka Chemical Industry Co., Ltd.), Tackirol 250-III (brominated alkylphenol formaldehyde resin, manufactured by Taoka Chemical Industry Co., Ltd.), PR-4507 (manufactured by Gunei Chemical Industry Co., Ltd.), Vulkaresat 510E (manufactured by Hoechst), Vulkaresat 532E (manufactured by Hoechst), Vulkaresen E (manufactured by Hoechst), Vulkaresen 105E (manufactured by Hoechst), Vulkaresen 130E (manufactured by Hoechst), Vulkaresol 315E (manufactured by Hoechst), Amberol ST 137X (manufactured by Rohm & Haas), SUMILITE RESIN PR-22193 (manufactured by Sumitomo Bakelite Co., Ltd.), Symphorm-C-100 (manufactured by Anchor Chem.), Symphorm-C-1001 (manufactured by Anchor Chem.), TAMANOL 531 (manufactured by Arakawa Chemical Industries, Ltd.), Schenectady SP1059 (manufactured by Schenectady Chem.), Schenectady SP1045 (manufactured by Schenectady Chem.), CRR-0803 (manufactured by UCC), Schenectady SP1055 (brominated alkylphenol formaldehyde resin, manufactured by Schenectady Chem.), Schenectady SP1056 (manufactured by Schenectady Chem.), CRM-0803 (manufactured by Showa High Molecular Co., Ltd.), and Vulkadur A (manufactured by Bayer). Among them, halogenated phenolic resin crosslinking agents are preferred, and brominated alkylphenol formaldehyde resins such as Tackirol 250-I, 250-III, Schenectady SP1055, and SP1056 are more preferred.
[0215] As specific examples of crosslinking using the phenolic resin-based crosslinking agent, the techniques described in US Pat. No. 4,311,628, US Pat. No. 2,972,600, and US Pat. No. 3,287,440 can also be used.
[0216] The specification of U.S. Patent No. 4,311,628 discloses a phenolic curative system composed of a phenolic curing resin and a cure activator. The basic component of the system is a phenolic resin crosslinking agent produced by condensing a substituted phenol (e.g., a halogen-substituted phenol, a C1-C2 alkyl-substituted phenol) or an unsubstituted phenol with an aldehyde, preferably formaldehyde, in an alkaline medium, or by condensing a difunctional phenol diol (preferably a dihydroxymethylphenol substituted at the para position by a C5-C10 alkyl). Particularly suitable is a halogenated alkyl-substituted phenolic resin crosslinking agent produced by halogenating an alkyl-substituted phenolic resin crosslinking agent. A phenolic resin crosslinking agent composed of a hydroxymethylphenol curing resin, a halogen donor, and a metal compound is particularly recommended, and its details are described in the specifications of U.S. Patent Nos. 3,287,440 and 3,709,840. The non-halogenated phenolic resin crosslinking agent is used together with a halogen donor, preferably together with a hydrogen halide scavenger. Generally, a halogenated phenolic resin crosslinking agent, preferably a brominated phenolic resin crosslinking agent containing 2 to 10% by mass of bromine, does not require a halogen donor, and can be used together with a hydrogen halide scavenger such as a metal oxide selected from iron oxide, titanium oxide, magnesium oxide, magnesium silicate, silicon dioxide and zinc oxide, preferably zinc oxide. These hydrogen halide scavengers such as zinc oxide are usually used in an amount of 1 to 20 parts by mass relative to 100 parts by mass of the phenolic resin crosslinking agent. The presence of such a scavenger promotes the crosslinking action of the phenolic resin crosslinking agent, but in the case of a rubber that is not easily crosslinked by the phenolic resin crosslinking agent, it is preferred to use a halogen donor and zinc oxide together. Their use in the preparation of halogenated phenolic curing resins and in the crosslinking agent system using zinc oxide is described in the specifications of U.S. Pat. No. 2,972,600 and U.S. Pat. No. 3,093,613, the disclosures of which are incorporated herein by reference together with the disclosures of the aforementioned U.S. Pat. No. 3,287,440 and U.S. Pat. No. 3,709,840. Examples of suitable halogen donors include halogen-donating polymers such as stannous chloride, ferric chloride, chlorinated paraffin, chlorinated polyethylene, chlorosulfonated polyethylene, and polychloroprene (chloroprene rubber). For more details on phenolic vulcanizing agent systems, please refer to "Vulcanization and Vulcanizing Agents" (W. Hoffman, Palmerton Publishing Company). Suitable phenolic resin-based crosslinking agents are commercially available, for example, such crosslinking agents can be purchased from Schenectady Chemicals, Inc. under the trade names "SP1045", "CRJ352", "SP1055", "SP1056".
[0217] The phenolic resin crosslinking agent is preferably used in an amount of 0.1 to 20 parts by mass, more preferably 1 to 10 parts by mass, based on 100 parts by mass of the component (a). The phenolic resin crosslinking agent may be used in the form of a crosslinking agent masterbatch prepared by mixing with a hydrogen halide scavenger such as zinc oxide.
[0218] By setting the blending amount of the phenolic resin crosslinking agent to the above range, a composition having excellent moldability can be easily obtained, and the obtained thermoplastic elastomer molded product has high strength, excellent oil resistance, and sufficient heat resistance and mechanical properties.
[0219] When the above-mentioned phenolic resin crosslinking agent is used for dynamic crosslinking, crosslinking aids such as sulfur, p-quinone dioxime, p,p'-dibenzoylquinone dioxime, N-methyl-N,4-dinitroaniline, nitrosobenzene, diphenylguanidine, trimethylolpropane-N,N'-m-phenylenedimaleimide, etc., and aids such as divinylbenzene, triallyl cyanurate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, allyl methacrylate, etc., and multifunctional vinyl monomers such as vinyl butyrate and vinyl stearate can be used.
[0220] By using the above auxiliary agent, a uniform and mild cross-linking reaction can be expected.
[0221] As the auxiliary agent, divinylbenzene is preferred. Divinylbenzene is easy to handle, has good compatibility with the uncrosslinked rubber (a-1) and the crystalline polyolefin (b-1), and has the function of solubilizing the phenolic resin crosslinking agent, and acts as a dispersant for the phenolic resin crosslinking agent. Therefore, the crosslinking effect due to the heat treatment becomes homogeneous, and a thermoplastic elastomer having a balance between fluidity and physical properties can be easily obtained.
[0222] The crosslinking aid or auxiliary agent is preferably used in an amount of 2 parts by mass or less, more preferably 0.3 to 1 part by mass, based on 100 parts by mass of the component (a).
[0223] Furthermore, when dynamic crosslinking is performed using the phenolic resin crosslinking agent, a dispersion accelerator may be used to promote dispersion of the phenolic resin crosslinking agent.
[0224] Examples of the dispersion accelerator include tertiary amines such as triethylamine, tributylamine, and 2,4,6-tris(dimethylamino)phenol; cyclopentanecarboxylates of aluminum, cobalt, vanadium, copper, calcium, zirconium, manganese, magnesium, lead, mercury, and cyclopentanecarboxylic acid and various metals (e.g., Pb, Co, Mn, Ca, Cu, Ni, Fe, Zn, and rare earths); and the like.
[0225] The amount of the dispersion promoter used is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the total of the component (a) and the component (b).
[0226] When the amount of the dispersion accelerator used is within the above range, the crosslinking reaction does not proceed too rapidly, and the dispersion accelerator is unlikely to remain unreacted in the obtained thermoplastic elastomer, so that a thermoplastic elastomer having excellent fluidity and hardly causing changes in physical properties due to thermal history during processing and molding can be easily obtained.
[0227] The aforementioned “dynamic heat treatment” means kneading the above-mentioned components in a molten state.
[0228] The kneading can be performed using a kneading device, and as the kneading device, a conventionally known kneading device such as an open type mixing roll, a non-open type Banbury mixer, an extruder, a kneader, a continuous mixer, etc. can be used. Among them, a non-open type kneading device is preferred.
[0229] The kneading is preferably performed in an atmosphere of an inert gas such as nitrogen or carbon dioxide.
[0230] The kneading temperature is usually 150 to 280° C., preferably 170 to 250° C., and the kneading time is usually 0.5 to 20 minutes, preferably 1 to 10 minutes.
[0231] The kneading is preferably performed while applying a shear force, and the applied shear force is preferably set at a shear rate of 10 to 50,000 sec. ~1 The range is preferably 100 to 20,000 seconds. ~1 range.
[0232] The thermoplastic elastomer preferably has a Shore D hardness (after 5 seconds) of 1 to 98, more preferably 1 to 60, further preferably 10 to 50, and particularly preferably 30 to 50 as measured in accordance with ISO 7619 in order to obtain a molded body with excellent rigidity.
[0233] The MFR of the thermoplastic elastomer measured at 230°C and a load of 10 kgf according to ASTM D1238 is usually 0.1 to 100 g / 10 min, preferably 1 to 100 g / 10 min. If the MFR is above the lower limit, the fluidity becomes good and molding in the extruder becomes easy. If the MFR is below the upper limit, the occurrence of drawdown can be suppressed when discharged from the die of the extruder, and the extrusion moldability becomes good.
[0234] <<Molding>>
[0235] The molded product according to one embodiment of the present invention (hereinafter also referred to as “the present molded product”) is a molded product obtained by molding the present composition.
[0236] The present molded product can be produced by molding the present composition using various known molding methods, specifically, by various molding methods such as extrusion molding, press molding, injection molding, calendar molding, and blow molding.
[0237] The present molded product may be a molded product obtained by subjecting a molded product such as a sheet obtained by the above-mentioned molding method to secondary processing such as thermoforming.
[0238] From the viewpoint of excellent moldability of the present molded body, the MFR of the present composition measured at 230°C and a load of 10 kgf according to ASTM D1238 is preferably 0.1 to 100 g / 10 min, and more preferably 1 to 100 g / 10 min. If the MFR is above the aforementioned lower limit, the fluidity becomes good and molding in the extruder becomes easy. If the MFR is below the aforementioned upper limit, the occurrence of drawdown can be suppressed when discharged from the die of the extruder, and the extrusion moldability becomes good.
[0239] The expansion value of the molded article is preferably 1.00 to 1.50, more preferably 1.03 to 1.10. When the expansion value is within the above range, the adhesion of the material deposit on the die may be suppressed, and the processability may be improved.
[0240] The Shore D hardness (after 5 seconds) of the molded article measured in accordance with ISO 7619 is preferably 30 to 60, more preferably 34 to 58, further preferably 38 to 56, and particularly preferably 42 to 54, from the viewpoint of obtaining a molded article with excellent rigidity.
[0241] The use of the molded article is not particularly limited, and various known uses such as automobile parts, civil engineering / building materials, electric / electronic parts, sanitary products, films / sheets, etc. can be cited as preferred examples.
[0242] <Automotive Parts>
[0243] Examples of the aforementioned automobile parts include automobile interior parts and automobile exterior parts. Specific examples include weather stripping materials, bumper trims, side trims, air spoilers, deflectors, fenders, air duct hoses, wire harness grommets, rack and pinion protective covers, suspension cover protective covers, glass guides, inner waistline seals, corner decorative parts, glass edging, hood seals, glass run channels, auxiliary seals, various gaskets, hoses, and airbag covers.
[0244] Among them, the molded article has an excellent balance between adhesiveness and slidability and is also excellent in low-temperature impact strength, and therefore is particularly suitable for automobile parts having corners such as glass run channels.
[0245] <Civil Engineering / Building Materials>
[0246] Examples of the civil engineering and building materials include foundation improvement sheets, water supply boards, civil engineering materials and building materials for noise prevention, various pads and sheets for civil engineering and construction, waterproof materials, joint materials, and window frames for buildings.
[0247] <Electrical / electronic components>
[0248] Examples of the electric / electronic components include electric / electronic components such as wire covering materials, connectors, caps, and plugs.
[0249] <Sanitary Products>
[0250] Examples of the sanitary products include sanitary products such as sanitary products, disposable diapers, and toothbrush handles.
[0251] <Film / Sheet>
[0252] Examples of the film / sheet include infusion bags, medical containers, automobile interior and exterior materials, beverage bottles, suitcases, food packaging materials, food containers, retort containers, tubes, transparent substrates, and sealants.
[0253] The present molded article can also be used for applications other than the above-mentioned applications.
[0254] As other uses, for example, there can be mentioned footwear such as soles and sandals; leisure products such as swimming fins, underwater goggles, golf club grips, and baseball bat grips; pads; waterproof cloths; belts; garden hoses; anti-slip tapes for steps; and anti-slip tapes for logistics pallets.
[0255] Example
[0256] Hereinafter, although embodiment examples of the present invention will be described in further detail, the present invention is not limited to these examples.
[0257] <Measurement or Evaluation Method>
[0258] In addition, below, each physical property was measured or evaluated by the following method.
[0259] [Double-layer sheet forming method]
[0260] The various double-layer sheets used in the evaluation of the sliding composition were produced by appropriately changing the type of substrate and the thickness of the sheet under the following conditions. The sliding layer used pellets of the sliding composition obtained below. The substrate layer was extruded using a 50 mm single-screw extruder (manufactured by Nippon Steel Works, Ltd.) under temperature conditions [C1 / C2 / C3 / C4 / C5=160 / 170 / 180 / 190 / 200°C]. In addition, the sliding layer was extruded using a 30 mm single-screw extruder (manufactured by Plastics Engineering Research Institute, Ltd.) under temperature conditions [C1 / C2 / C3=200 / 210 / 230°C].
[0261] [Weight average molecular weight]
[0262] The weight average molecular weights of the (co)polymer and the organosilicon compound were measured by GPC under the following conditions.
[0263] (Measurement conditions)
[0264] Equipment: HLC-8120 manufactured by Tosoh Corporation
[0265] Column: PL 10u Mixed B manufactured by Polymer Laboratories (7.5 mm ID×30 cm×2)
[0266] Detector: Differential refractive index detector (RI / built-in)
[0267] Solvent: Toluene (special grade)
[0268] Temperature: 40℃
[0269] Flow rate: 1.0mL / min
[0270] Injection volume: 110 μL
[0271] Concentration: 0.1 mass%
[0272] Calibration sample: monodisperse polystyrene
[0273] Calibration method: Polystyrene conversion
[0274] [Intrinsic viscosity [η] measured in decalin at 135°C]
[0275] The intrinsic viscosity [η] (dl / g) of the (co)polymer was measured in decalin at a temperature of 135°C.
[0276] Specifically, about 15 mg of the sample was dissolved in 50 ml of decalin, and the specific viscosity η was measured in an oil bath at 135°C. sp After adding 5 ml of decahydronaphthalene to dilute the decahydronaphthalene solution, the specific viscosity η was measured in the same manner. spThis dilution operation was repeated twice, and the concentration (C) was extrapolated to 0 as shown in the following formula to obtain η sp The value of / C is taken as the intrinsic viscosity [η].
[0277] [η] = lim(η sp / C)(C→0)
[0278] [Average particle size D 50 ]
[0279] The average particle size D of ultra-high molecular weight polyethylene 50 The particle size distribution was calculated from the weight-based particle size distribution by the Coulter counter method using Multisizer Three manufactured by Beckman Coulter.
[0280] [Melting point (Tm)]
[0281] The melting point (Tm) of the (co)polymer was measured by differential scanning calorimetry using the following method.
[0282] About 5 mg of the sample was placed in a special aluminum pan, and the temperature was raised from 30°C to 230°C at 320°C / min using Diamond DSC manufactured by PerkinElmer Japan, and after being kept at 230°C for 10 minutes, the temperature was lowered from 230°C to 30°C at 10°C / min, and further kept at 30°C for 1 minute, and then the temperature was raised at 10°C / min, and the melting point was obtained from the endothermic curve at this time. It should be noted that when multiple peaks are detected during DSC measurement, the peak temperature detected on the highest temperature side is defined as the melting point (Tm).
[0283] [Ethylene content]
[0284] The ethylene content of the copolymer was determined under the following conditions: 13 The content was calculated based on the analysis of the spectrum obtained by C-NMR measurement.
[0285] Equipment: AVANCEIIICryo-500 nuclear magnetic resonance equipment manufactured by Bruker BioSpin
[0286] Measuring nucleus: 13C (125MHz)
[0287] Measurement mode: Single pulse proton broadband decoupling
[0288] Pulse width: 45° (5.00μs)
[0289] Points: 64k
[0290] Measuring range: 250ppm (-55~195ppm)
[0291] Repeat time: 5.5 seconds
[0292] Total times: 128 times
[0293] Determination solvent: o-dichlorobenzene / benzene-d6 (4 / 1 [v / v])
[0294] Sample concentration: ca.60mg / 0.6mL
[0295] Measuring temperature: 120℃
[0296] Window function: Exponential (BF: 1.0Hz)
[0297] Chemical shift reference: δδ signal (29.73ppm)
[0298] [Iodine value]
[0299] Iodine value of copolymer The iodine value (g / 100 g) of the following ethylene-propylene-5-ethylidene-2-norbornene copolymer rubber was measured in accordance with JIS K 0070:1992.
[0300] [Melt flow rate (MFR)]
[0301] The MFR of the sliding composition obtained below was measured at 230° C. and a load of 10 kgf in accordance with ASTM D1238.
[0302] In addition, the MFR of the raw material (co)polymer used in the following Examples and Comparative Examples was measured at 230°C or 190°C and a load of 2.16 kgf in accordance with JIS K 7210.
[0303] [Shore D hardness (after 5 seconds)]
[0304] According to ISO 7619, a 3 mm thick injection molded square plate was prepared using the sliding composition obtained below. A 6 mm thick laminated sheet obtained by stacking two 3 mm thick injection molded square plates was used to measure the Shore D hardness of the square plate using a Shore D hardness tester. The Shore D hardness was determined after 5 seconds of measurement.
[0305] [Tensile properties (tensile breaking strength and tensile breaking elongation)]
[0306] A 2 mm thick pressed sheet was prepared from the sliding composition obtained below using a 50 t press machine (equipment conditions: preheating (190° C.) for 8 minutes, pressing (190° C.) for 6 minutes) to prepare a 2 mm thick pressed sheet. The prepared 3 mm thick pressed sheet was subjected to a tensile test in accordance with JIS K 6251 using a JIS No. 3 dumbbell at a measuring temperature of 25° C. and a tensile speed of 500 mm / min and 200 mm / min to measure the tensile breaking strength (TB) and tensile breaking elongation (EB).
[0307] [Sliding characteristics (dynamic friction coefficient and wear amount)]
[0308] A soft thermoplastic elastomer material with a hardness of 70° (C700BM manufactured by Mitsui Chemicals, Inc.) was used as a substrate, and the sliding composition obtained below was laminated on the substrate to a thickness of 200 μm using an extruder to prepare a two-layer sheet. A glass sheet with a thickness of 2 mm, a radius R of 10 mm at the tip, and a surface roughness Ra of 3.0 μm was brought into contact with the surface of the sliding composition side of the prepared two-layer sheet, and slid 20,000 times at a load of 1 kg, a speed of 150 mm / sec, and a sliding distance of 100 mm.
[0309] The dynamic friction coefficient after sliding and the dynamic friction coefficient before sliding were measured in accordance with ASTM D1894-63. If the dynamic friction coefficient after sliding is 0.25 or less, it can be said that the sliding characteristics are excellent.
[0310] The wear amount was calculated by weighing the mass (mg) of the sliding composition before and after sliding.
[0311] [Extrusion processability (adhesion of deposited material)]
[0312] A soft thermoplastic elastomer material with a hardness of 70° (C700BM manufactured by Mitsui Chemicals, Inc.) was used as a substrate, and the sliding composition obtained below was laminated on the substrate to a thickness of 200 to 250 μm using an extruder for 30 minutes to produce a two-layer sheet.
[0313] After the molding was continued for 30 minutes, the extrusion processability of the slidable composition was evaluated according to the following criteria.
[0314] 0:No silicone deposits are attached to the die of the extruder
[0315] ×: Silicone deposits adhere to the die of the extruder.
[0316] [Extrusion processability (molding appearance)]
[0317] For the two-layer sheet produced in the evaluation of sliding properties, the surface roughness of the sliding composition side before sliding was observed using a surface roughness measuring instrument (model: VR-5000, manufactured by KEYENCE), a comparative measurement module (model: VR-H3J, manufactured by KEYENCE) and a VR-5000 analysis application (manufactured by KEYENCE) to obtain the ten-point average roughness Rz of the surface roughness. The molded appearance was evaluated according to the following criteria.
[0318] ○: Rz less than 30μm
[0319] ×: Rz is 30 μm or more
[0320] [Extrusion processability (expansion)]
[0321] The pellets of the sliding composition obtained below were measured at a shear rate of 122 sec at a measurement temperature of 200° C. and a residual heat time of 6 minutes using a Strograph 1D model (hole L / D=30) manufactured by Toyo Seiki Seisaku-sho. -1 The expansion value at .
[0322] [Adhesion]
[0323] To the two-layer sheet produced in the evaluation of sliding properties, a thermoplastic elastomer for injection bonding (Milastomer G800BS manufactured by Mitsui Chemicals, Inc.) was bonded by injection molding to produce a test piece.
[0324] The bonding interface of the obtained test piece was repeatedly bent 180 degrees, and the number of times of bending until a notch was generated at the end of the test piece or the test piece was broken was evaluated according to the following criteria.
[0325] 0:Bending times: 30 times or more
[0326] ×: Bending times less than 30 times
[0327] [Heat aging resistance]
[0328] A substrate A (C700BM manufactured by Mitsui Chemicals, Inc.) having a JIS DuroA hardness of 70° and an oil filling amount of 40 parts by mass, or a substrate B (TS7000N manufactured by Mitsui Chemicals, Inc.) having a JIS DuroA hardness of 70° and an oil filling amount of 50 parts by mass was used as a substrate, and the sliding composition obtained below was laminated on the substrate in a manner to a thickness of 200 μm using an extrusion molding machine to prepare a two-layer sheet.
[0329] Each of the obtained two-layer sheets was heated at 85° C. for 72 hours, and the surface of each two-layer sheet on the side of the slidable composition after heating was observed. Changes before and after heating were evaluated according to the following criteria.
[0330] ○: No changes were observed for the double-layer tablets before and after heating
[0331] ×: Changes such as oozing out were observed on the surface of the double-layer sheet before and after heating.
[0332] <Materials used>
[0333] As the component (α) containing the ethylene-α-olefin-non-conjugated polyene copolymer (A), the following oil-extended rubber was used.
[0334] Oil-extended rubber (α-1): Mitsui EPT (registered trademark) 3072EPM (manufactured by Mitsui Chemicals, Inc.)
[0335] The oil-extended rubber (α-1) is an oil-extended ethylene-propylene-5-ethylidene-2-norbornene (ENB) copolymer rubber obtained by oil-extending an ethylene-propylene-ENB copolymer (A-1) having an ethylene content of 64 mass% (molar conversion value (the total of ethylene and propylene is 100 mole%); ethylene content of 75.8 mole%, propylene content of 24.2 mole%), an ENB content of 5.4 mass%, an iodine value of 11.5 g / 100 g, an intrinsic viscosity [η] measured in decalin at 135° C. of 3.4 dl / g, and a weight average molecular weight of 280,000 (oil-extending amount of 40 parts by mass). It should be noted that the oil-extending amount of 40 parts by mass means that 40 parts by mass of a petroleum-based plasticizer (softener) are blended with 100 parts by mass of the ethylene-propylene-ENB copolymer (A-1).
[0336] Oil-extended rubber (α-2): Mitsui EPT (registered trademark) 4100E (manufactured by Mitsui Chemicals, Inc.)
[0337] The oil-extended rubber (α-2) is an oil-extended ethylene-propylene-ENB copolymer rubber, obtained by oil-extending an ethylene-propylene-ENB copolymer (A-2) having an ethylene content of 57% by mass (molar conversion value (the total of ethylene and propylene is 100% by mole); ethylene content of 71% by mole, propylene content of 29% by mole), an ENB content of 7.3% by mass, an iodine value of 15.4 g / 100 g, an intrinsic viscosity [η] measured in decalin at 135° C. of 4.1 dl / g, and a weight average molecular weight of 470,000 (oil-extending amount: 50 parts by mass).
[0338] Oil-extended rubber (α-3): Mitsui EPT (registered trademark) X-3042 (manufactured by Mitsui Chemicals, Inc.)
[0339] The oil-extended rubber (α-3) is an oil-extended ethylene-propylene-ENB copolymer rubber, obtained by oil-extending an ethylene-propylene-ENB copolymer (A-3) having an ethylene content of 67% by mass (molar conversion value (the total of ethylene and propylene is 100% by mole); ethylene content of 77% by mole, propylene content of 23% by mole), an ENB content of 4.3% by mass, an iodine value of 9.9 g / 100 g, an intrinsic viscosity [η] measured in decalin at 135° C. of 4.3 dl / g, and a weight average molecular weight of 350,000 (oil-extending amount: 120 parts by mass).
[0340] As the propylene-based random copolymer (B1), the following copolymers were used.
[0341] ·Copolymer (B1-1): Prime Polypro B241 (manufactured by Prime Polymer Co., Ltd.)
[0342] The copolymer (B1-1) is a crystalline resin of a propylene / ethylene random copolymer, and has an MFR (according to JIS K7210, 190°C, 2.16 kgf load) of 0.5 g / 10 min and a density of 910 kg / m 3 .
[0343] As the propylene homopolymer (B2), the following polymers were used.
[0344] Homopolymer (B2-1): Prime Polypro E200 GP (manufactured by Prime Polymer Co., Ltd.)
[0345] The homopolymer (B2-1) had an MFR (according to JIS K 7210, 190°C, 2.16 kgf load) of 2.0 g / 10 min and a density of 900 kg / m 3 .
[0346] Homopolymer (B2-2): Prime Polypro E111G (manufactured by Prime Polymer Co., Ltd.)
[0347] The homopolymer (B2-2) had an MFR (according to JIS K 7210, 190°C, 2.16 kgf load) of 0.5 g / 10 min and a density of 910 kg / m 3 .
[0348] As the high-density polyethylene (C1) and the high-density polyethylene for comparative example (C1′), the following copolymers were used.
[0349] Polyethylene (C1-1): Hi-zex8200B (manufactured by Prime Polymer Co., Ltd.)
[0350] The MFR (according to JIS K 7210, 190°C, 2.16 kgf load) of polyethylene (C1-1) is 0.03 g / 10 min, and the density is 952 kg / m 3 .
[0351] Polyethylene (C1'-1): Hi-zex5000S (manufactured by Prime Polymer Co., Ltd.)
[0352] The MFR (according to JIS K 7210, 190°C, 2.16 kgf load) of polyethylene (C1'-1) is 0.82 g / 10 min, and the density is 949 kg / m 3 .
[0353] Polyethylene (C1'-2): Hi-zex2200J (manufactured by Prime Polymer Co., Ltd.)
[0354] The MFR (according to JIS K 7210, 190°C, 2.16 kgf load) of polyethylene (C1'-2) is 5.20 g / 10 min, and the density is 964 kg / m 3 .
[0355] As the ultra-high molecular weight polyethylene (C2) and the ultra-high molecular weight polyethylene for comparative example (C2′), the following copolymers were used.
[0356] Polyethylene (C2-1): MIPELON XM-220 (manufactured by Mitsui Chemicals, Inc.)
[0357] The intrinsic viscosity [η] of polyethylene (C2-1) measured in decalin at 135°C is 28.0 dl / g, and the average particle size D 50 30μm, density 938kg / m 3 .
[0358] Polyethylene (C2'-1): MIPELON PM-200 (manufactured by Mitsui Chemicals, Inc.)
[0359] Average particle size D of polyethylene (C2'-1) 50 10μm, density 938kg / m 3 .
[0360] Polyethylene (C2'-2): MIPELON XM-330 (manufactured by Mitsui Chemicals, Inc.)
[0361] The weight average molecular weight of polyethylene (C2'-2) is 2 million, the intrinsic viscosity [η] measured in decalin at 135°C is 28.5 dl / g, and the average particle size D 50 65μm, density 938kg / m 3.
[0362] As the organosilicon compound (D), the following organosilicon master batches or silicone oils were used.
[0363] Compound (D-1): MB50-001 (manufactured by Dow Corning Toray Co., Ltd.)
[0364] Compound (D-1) is a silicone masterbatch, which is a pellet obtained by dispersing a silicone rubber having a kinematic viscosity of 1,000,000 cSt at 25°C in polypropylene (the aforementioned component (B3)), and the silicone rubber content is 50% by mass.
[0365] Compound (D-2): KF96-60000 CS (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0366] Compound (D-2) is a silicone oil having a kinematic viscosity of 60,000 cSt at 25°C.
[0367] Compound (D-3): KF96-3000CS (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0368] Compound (D-3) is a silicone oil having a kinematic viscosity of 3000 cSt at 25°C.
[0369] As the crosslinking agent, a masterbatch of the following phenolic resin crosslinking agent or organic peroxide crosslinking agent was used.
[0370] Phenolic resin crosslinking agent masterbatch (CL-1): a mixture of a phenolic resin crosslinking agent (SP-1055, manufactured by Schenectady Chemicals, Inc.) and zinc oxide (mass ratio = 10:1)
[0371] Organic peroxide crosslinking agent masterbatch (CL-2): a mixture of an organic peroxide crosslinking agent (PERHEXA25B, manufactured by NOF Corporation), divinylbenzene (DVB810, manufactured by NS Styrene Monomer) and a softener (E-1) described below (mass ratio = 5:2:3)
[0372] As other components, the following additives were used.
[0373] Softener (E-1): Diana Process PW-90 (manufactured by Idemitsu Kosan Co., Ltd., paraffin oil)
[0374] Colorant: F32387MM (manufactured by DIC Corporation, carbon black masterbatch, mass ratio (mass %): polyethylene (the above-mentioned component (C3)) / carbon = 60 / 40)
[0375] · Antioxidant: AO-60 (manufactured by ADEKA Co., Ltd., phenolic antioxidant)
[0376] Ultraviolet light absorber: Tinuvin 326FL (manufactured by BASF Japan, benzotriazole-based ultraviolet light absorber)
[0377] Weathering stabilizer: Tinuvin 770 (manufactured by BASF Japan, hindered amine (HALS) weathering stabilizer)
[0378] Other additives: ALFLOW P10 (manufactured by NOF Corporation, fatty acid amide)
[0379] <Manufacturing of Thermoplastic Elastomer (EL)>
[0380] [Production Example 1]
[0381] 46.9 mass % of oil-extended rubber (α-1) (33.3 mass % based on copolymer (A-1)), 11.7 mass % of homopolymer (B2-1), 8.4 mass % of homopolymer (B2-2), 2.95 mass % of phenolic resin crosslinking agent masterbatch (CL-1) as a crosslinking agent, 0.07 mass % of antioxidant, 0.07 mass % of ultraviolet absorber, 0.03 mass % of weathering stabilizer, 1.3 mass % of carbon black masterbatch and 28.5 mass % of softener (E-1) were fully mixed using a Henschel mixer and extrusion kneaded under the following conditions to produce a thermoplastic elastomer (EL1) in which at least a portion of the copolymer (A) was crosslinked with a phenolic resin crosslinking agent.
[0382] In addition, the content (mass %) of each component (A), (B2) and (E) relative to 100.0 mass % of the obtained thermoplastic elastomer is shown in Table 1 as a composition ratio.
[0383] (Mixing conditions)
[0384] Extruder: Product No. KTX-46, manufactured by Kobe Steel, Ltd.
[0385] Cylinder temperature: C1~C2 120℃, C3~C4 140℃, C5~C14 200℃
[0386] Mold temperature: 200℃
[0387] Screw speed: 400rpm
[0388] Extrusion capacity: 80kg / h
[0389] [Production Examples 2 to 4]
[0390] Thermoplastic elastomers (EL2) to (EL4) were obtained in the same manner as in Production Example 1 except that the types and blending amounts of the components were changed as shown in Table 1.
[0391] Thermoplastic elastomers (EL2) and (EL3) are copolymers (A) at least partially crosslinked with a phenolic resin crosslinking agent, and thermoplastic elastomer (EL4) is copolymer (A) at least partially crosslinked with an organic peroxide crosslinking agent.
[0392] [Table 1]
[0393]
[0394] <Manufacturing of Slidable Composition>
[0395] [Example 1]
[0396] 22.2 mass % of the thermoplastic elastomer (EL1) obtained in Production Example 1, 9.1 mass % of the copolymer (B1-1), 9.1 mass % of the homopolymer (B2-2), 31.6 mass % of the polyethylene (C1-1), 10.6 mass % of the polyethylene (C2-1), 8.5 mass % of the organosilicon compound (D-1), 2.4 mass % of the organosilicon compound (D-3), 0.05 mass % of the antioxidant, 0.18 mass % of the ultraviolet absorber, 0.05 mass % of the weathering stabilizer, 4.5 mass % of the carbon black masterbatch and 1.82 mass % of the fatty acid amide were fully mixed with a Henschel mixer and extruded and kneaded under the following conditions to obtain pellets of a sliding composition. The various physical properties of the molded body produced using the pellets of the obtained composition were evaluated according to the above method. The results are shown in Table 3.
[0397] In addition, the content (mass %) of each component (A), (B1), (B2), (C1), (C2), (D) and (E) relative to 100.0 mass % of the obtained sliding composition is shown in Table 3 as a composition ratio.
[0398] (Mixing conditions)
[0399] Extruder: Product No. KTX-46, manufactured by Kobe Steel, Ltd.
[0400] Cylinder temperature: C1~C2 120℃, C3~C4 140℃, C5~C14 200℃
[0401] Mold temperature: 200℃
[0402] Screw speed: 400rpm
[0403] Extrusion capacity: 80kg / h
[0404] [Examples 2 to 8 and Comparative Examples 1 to 9]
[0405] In Example 1, except that the types and blending amounts of each component were changed as described in Table 2, the same operation as in Example 1 was carried out to produce pellets of a sliding composition. Various physical properties of a molded body produced using the pellets of the obtained composition were evaluated according to the above methods. The results are shown in Table 3.
[0406] [Table 2]
[0407]
[0408] [Table 3]
[0409]
Claims
1. A sliding composition comprising: 7.0% by mass or more of ethylene-α-olefin-non-conjugated polyene copolymer (A), 6.0% by mass or more of a propylene random copolymer (B1) having a melt flow rate of 0.1 to 4.0 g / 10 min as measured at 190° C. and a load of 2.16 kgf, 10.0% by mass or more of a propylene homopolymer (B2) having a melt flow rate of 0.1 to 4.0 g / 10 min as measured at 190° C. and a load of 2.16 kgf, Density: 940~970kg / m 3 15.0% by mass or more of a high-density polyethylene (C1) having a melt flow rate of 0.1 g / 10 min or less measured at 190° C. and a load of 2.16 kgf, The intrinsic viscosity η measured in decalin solvent at 135°C is 10 to 40 dl / g, and the average particle size D 50 22~50μm, density less than 940kg / m 3 10.0 mass % or more of ultra-high molecular weight polyethylene (C2), and 5.0 to 8.0 mass % of an organosilicon compound (D) having a kinematic viscosity of 3,000 to 1,000,000 cSt at 25°C; The total content of the components (A), (B1), (B2), (C1), (C2) and (D) is 100.0% by mass or less, At least a part of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is crosslinked with a phenolic resin-based crosslinking agent.
2. The sliding composition according to claim 1, further comprising 0.1 to 10.0 mass % of a softener (E), The total content of the components (A), (B1), (B2), (C1), (C2), (D) and (E) is 100.0% by mass or less, The weight average molecular weight of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is greater than 280,000, the intrinsic viscosity η measured in decalin at 135°C is greater than 3.4 dl / g, the content of the structural units derived from ethylene is less than 70% by mass when the total content of the structural units derived from ethylene and the structural units derived from α-olefin is 100% by mass, and the content of the structural units derived from the non-conjugated polyene accounts for less than 6.0% by mass of all the structural units of the copolymer (A).
3. The sliding composition according to claim 1 or 2, wherein The Shore D hardness measured in accordance with ISO 7619 after 5 seconds of measurement is 30 to 60.
4. The sliding composition according to claim 1 or 2, wherein The content of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is 7.0 to 10.0% by mass.
5. The sliding composition according to claim 1 or 2, wherein The total content of the propylene random copolymer (B1) and the propylene homopolymer (B2) is 20.0% by mass or more.
6. The sliding composition according to claim 1 or 2, wherein The content of the propylene random copolymer (B1) is 9.0 to 15.0% by mass, and the density of the propylene random copolymer (B1) is 900 to 920 kg / m 3 .
7. The sliding composition according to claim 1 or 2, wherein The content of the propylene homopolymer (B2) is 10.0 to 18.0% by mass, and the density of the propylene homopolymer (B2) is 900 to 920 kg / m 3 .
8. The sliding composition according to claim 1 or 2, wherein The mass ratio of the propylene homopolymer (B2) to the propylene random copolymer (B1), that is, (B2) / (B1), is 1.0 to 3.
0.
9. The sliding composition according to claim 1 or 2, wherein The content of the ultra-high molecular weight polyethylene (C2) is 10.0-30.0% by mass, and the average particle size D 50 22~30μm.
10. A molded product obtained by molding the sliding composition according to claim 1 or 2. A glass run channel comprising the molded article according to claim 10 .
12. A method for producing a sliding composition, the sliding composition comprising: 7.0% by mass or more of ethylene-α-olefin-non-conjugated polyene copolymer (A), 6.0% by mass or more of a propylene random copolymer (B1) having a melt flow rate of 0.1 to 4.0 g / 10 min as measured at 190° C. and a load of 2.16 kgf, 10.0% by mass or more of a propylene homopolymer (B2) having a melt flow rate of 0.1 to 4.0 g / 10 min as measured at 190° C. and a load of 2.16 kgf, Density: 940~970kg / m 3 15.0% by mass or more of a high-density polyethylene (C1) having a melt flow rate of 0.1 g / 10 min or less measured at 190° C. and a load of 2.16 kgf, The intrinsic viscosity η measured in decalin solvent at 135°C is 10 to 40 dl / g, and the average particle size D 50 22~50μm, density less than 940kg / m 3 10.0 mass % or more of ultra-high molecular weight polyethylene (C2), and 5.0 to 8.0% by mass of an organosilicon compound (D) having a kinematic viscosity of 3,000 to 1,000,000 cSt at 25°C The total content of the components (A), (B1), (B2), (C1), (C2) and (D) is 100.0% by mass or less, At least a portion of the ethylene-α-olefin-non-conjugated polyene copolymer (A) is cross-linked; The method for producing the sliding composition comprises the step of cross-linking at least a portion of the ethylene-α-olefin-non-conjugated polyene copolymer (A) with a phenolic resin-based cross-linking agent.
Citation Information
Patent Citations
Norbornene compound containing chain polyene group and its production, unsaturated ethylenic copolymer using the same and its production, and rubber composition containing the same copolymer
JP1997040586A
Production of ethylene / Alpha-olefin / Non-conjugated polyene random copolymer, ethylene / Alpha-olefin / Non-conjugated polyene random copolymer and use of the same
JP1997071617A
Ethylene / Alpha-olefin / Non-conjugated polyene random copolymer, rubber composition and their production
JP1997071618A
Preparation of solid titanium catalyst component, catalyst, and method for polymerizing olefin
JP1997208615A
Higher alpha-olefin copolymer and use of vulcanizate thereof
JP1998067823A